Efeitos do treinamento f??sico na cardiomiopatia e neuropatia auton??mica associadas ao diabetes tipo 2 em f??meas - Conti, Filipe Fernandes (2016)
Diabetic patients frequently present cardiomyopathy and autonomic neuropathy, which increases mortality risk. On the other hand, exercise training has been suggested as a non-pharmacological tool in the prevention and treatment of type 2 diabetes. However, there are few studies that evaluated the effects of the three types of exercise training, aerobic, resistance or combined, mainly in the female sex, on diabetic cardiomyopathy and autonomic neuropathy. Thus, the objective of this study was to evaluate the effects of exercise training on cardiac and autonomic changes in female mice with a model of type 2 diabetes associated or not with myocardial infarction. To better understand and analyze the data, we divided the thesis into three protocols with specific objectives: 1) to describe the use of the ECG platform coupled to the echocardiogram machine for the acquisition of cardiac signals used in the analysis of heart rate variability in trained and sedentary (Protocol 1); 2) to analyze the effects of three types of exercise training (aerobic, resistance and combined) on cardiac and autonomic function parameters in ob/ob female mice, a model of type 2 diabetes (Protocol 2); 3) to evaluate the effects of aerobic exercise training on cardiac, autonomic, oxidative stress and inflammation parameters in ob/ob female mice submitted to myocardial infarction (MI) (Protocol 3). In protocol 1, a new approach to the acquisition of the RR interval in mice for the analysis of heart rate variability (HRV) using the echocardiographic machine was described. This method was tested in sedentary mice and trained mice submitted to a protocol of exercise training in the wheel (8 weeks), proving the improvement of cardiac function and autonomic modulation in the trained group. In the protocol 2, ob/ob animals (group O) presented additional body weight gain, hyperglycemia, glucose intolerance, reduction of sympathetic and vagal modulation and impairment in diastolic function parameters in relation to control animals (group C), showing a development of diabetic cardiomyopathy and diabetic autonomic neuropathy. The animals submitted to aerobic training (OTA group, treadmill: 40-60% maximum test, 8 weeks) and combined (OTC group, treadmill + ladder in alternate days: 40-60% maximum capacity, 8 weeks) showed improvement of diastolic function and myocardial global index (MPI ??? C: 0.48??0.01, O: 0.59??0.04, OTA: 0.37??0.02, OTR: 0.51??0,05; OTC: 0.33??0.02) in relation to the O and resistance (OTR) groups. There was an improvement in HRV in the OTA group in relation to the other ob/ob groups (cardiac vagal modulation (AF - O: 12??3, OTA: 20??6, OTR: 9??3, OTC: 7??2 ms2). Correlations between the improvement of the cardiac vagal modulation and the attenuation of the ventricular dysfunction were observed. In addition, the three types of exercise training attenuated the body weight gain in obese animals, as well as reduced glycemia and glucose intolerance. In protocol 3, myocardial infarction (OIS group) reduced exercise capacity, cardiac function (ejection fraction - O: 68.0??2.0 vs. OIS: 49.5??4.8%), and HRV (RMSSD - O: 5.9??0.7 vs. OIS: 0.7??1 ms; SD1 - O: 4.2??0.5 vs. OIS: 0.5??0.1 ms; SD2 - O: 13.6??2.1 vs. OIS: 2.0??7.5 ms), increased pro-inflammatory profile (increase of IL-17 and reduction of IL-10) and increased oxidative stress (lipoperoxidation- O: 2,92 ?? 0,37 vs. OIS: 6.53 ?? 1.05 ??mol/mg protein; Protein oxidation - O: 8.46??0.61 vs. OIS: 13.02??1.20 nmol/mg protein) in ob/ob female mice. On the other hand, aerobic exercise training (treadmill: 40-60% maximal test, 4 weeks) post-MI in ob/ob females, despite not modifying cardiac function, improved exercise capacity, as well as HRV (RMSSD - 2.8??0.7 ms, SD1- 2.0??0.5 ms, SD2 ??? 7.5??1.2 ms), the inflammatory profile (reduction of IL-17 and increase of IL-10) and oxidative stress (lipoperoxidation - 4.18??0.3 ??mol / mg protein; Protein oxidation - 10.18 ?? 0.55 nmol / mg protein). In conclusion, even before the establishment of severe hyperglycemia, the development of type 2 diabetes in ob/ob females is associated with cardiac and autonomic dysfunctions, which are attenuated by resistance training, but mainly by aerobic or combined exercise training. In addition, myocardial infarction is associated with exacerbation of diabetic cardiomyopathy and autonomic neuropathy in females, and aerobic exercise training has a beneficial role in autonomic modulation, inflammation and cardiac oxidative stress in this condition. Taken together, our findings reinforce the important role of exercise training in managing cardiac and autonomic dysfunctions associated with complications of type 2 diabetes in females.